An investigation on the cash flow management system at Mvuma District Hospital 2013-2015 - Makoto, Wayne N. (Midlands State University, 2017)
This research was undertaken to investigate the effectiveness of cash flow management system at Mvuma District Hospital. The main problem was that Mvuma District Hospital was operating with most of its cash lying idle in debtors such that they were not able to pay their creditors and they had more expenses compared to income so this research was on the background of trying to enhance the cash flow management system at the hospital and improve the day to day running of the hospital. The research goes in depth by identifying the symptoms of poor cash flow management in hospitals. It gave theoretical evidence and theoretical evidence of ineffective cash flow management system in hospitals. This study was done using the descriptive research design using the Census technique. The census method was used in the selection of the sample size. Data was collected using questionnaires and one on one interview. The collected data was presented by using tables and pie charts. The major findings were that the sources of revenue were not being fully utilised and there poor management of receivables and payables. Budgets were not being followed as planned and there was no enough equipment to use at the hospital which is a symptom of poor cash flow management system. The recommendations were that the hospital must revisit its credit policy and also there need to make use of the closed departments at the hospital so as to generate more revenue for the hospital.